2002
DOI: 10.1034/j.1600-0706.2002.980213.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoids induce production of the dispersal morph of the pea aphid, Acyrthosiphon pisum

Abstract: In animals, inducible morphological defences against natural enemies mostly involve structures that are protective or make the individual invulnerable to future attack. In the majority of such examples, predators are the selecting agent while examples involving parasites are much less common. Aphids produce a winged dispersal morph under adverse conditions, such as crowding or poor plant quality. It has recently been demonstrated that pea aphids, Acyrthosiphon pisum, also produce winged offspring when exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 44 publications
2
100
0
Order By: Relevance
“…that there is low cross-immunity), mothers are expected to invest more in the immune protection of the philopatric, non-dispersing morph, than on the dispersing one. This prediction could be tested in insects producing both apterous and winged (alate) forms, such as aphids [51][52][53], ants [54,55], and termites [56], or in species that exhibit a sex-biased dispersal, such as gypsy moths [57] and midges [57]. In each of these cases, the philopatric morph or sex is expected to accrue greater benefits from a higher maternal investment in immunity than the dispersing one.…”
Section: Discussionmentioning
confidence: 99%
“…that there is low cross-immunity), mothers are expected to invest more in the immune protection of the philopatric, non-dispersing morph, than on the dispersing one. This prediction could be tested in insects producing both apterous and winged (alate) forms, such as aphids [51][52][53], ants [54,55], and termites [56], or in species that exhibit a sex-biased dispersal, such as gypsy moths [57] and midges [57]. In each of these cases, the philopatric morph or sex is expected to accrue greater benefits from a higher maternal investment in immunity than the dispersing one.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental work with the pea aphid, Acyrthosiphon pisum, found that alate (winged morph) production could be induced by the presence of a predator such as a ladybird (Sloggett & Weisser, 2002). For most species, this effect has not been considered, although predator-induced prey dispersal is likely to have some interesting consequences for the stability of spatial predator-prey systems.…”
Section: ( C ) Interspecific Interactionsmentioning
confidence: 99%
“…In contrast, the mere presence of particular natural enemies may elicit an increase in winged morph production in the pea aphid, Acyrthosiphon pisum (Dixon and Agarwala, 1999;Weisser et al, 1999;Sloggett and Weisser, 2002;Kunert and Weisser, 2003) (parasitization may also directly affect wing development, see below). The induction of winged morphs seems to result from increased tactile stimulation triggered by either predator avoidance behavior or from the release of aphid alarm pheromone .…”
Section: Interspecific Interactionsmentioning
confidence: 99%